Workshop Interactive Whispering Games untuk Meningkatkan Kemampuan Pronunciation Siswa SMPI Anharul Ulum di Lingkungan Pesantren Anharul Ulum Blitar - Dewi, Ekka Zahra Puspita; Ngaisah, Siti; Hira, Salma; Safitri, Ana; Maharani, Wening Pangesthi; Wijaya, Ade Taruna; Wulandari, Recavery Dwi; Jamil, Awaludin; Muarifah, Siti; Alfin, Charumin; Atmaja, Adi Tri; Musaiyaroh, Ati; Meinina, Rafiqa Ilma; Haryuni, Nining (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to improve the English pronunciation skills of students at Anharul Ulum Islamic Junior High School, Blitar Regency, particularly in a pesantren-based educational context. Prior to the program, by conducting a pre-test, the students demonstrated moderate to low pronunciation proficiency, characterized by limited accuracy in segmental and suprasegmental features, low fluency, and a lack of confidence in oral production. To address these issues, the program was implemented through three stages: introduction, implementation, and evaluation. During the implementation stage, Interactive Whispering Games were employed as a game-based learning strategy to promote active participation, collaborative learning, and reduced speaking anxiety. The effectiveness of the program was evaluated through pre-test and post-test assessments involving 53 students, complemented by observation and reflective feedback from students and teachers. The results revealed improvements across all assessed pronunciation aspects, with the highest increase observed in fluency, indicating enhanced spontaneity and confidence in oral production. Qualitative findings further showed increased student engagement, motivation, and positive attitudes toward pronunciation practice. Overall, the program demonstrates that Interactive Whispering Games are an effective, low-technology, and contextually appropriate approach for enhancing pronunciation skills in pesantren-based junior high schools and offer a practical model for similar community service initiatives. Overall, the program highlights the effectiveness of game-based learning strategies for supporting pronunciation development in a pesantren-based junior high school environment and offers a practical model for similar community service initiatives.